UNICEF's Role as a Norm Entrepreneur in Children's Education in South Sudan - Romia, Queena Aliyah (JLAST : Journal of Law and Social Transformation, 2025)
Abstrak Sudan Selatan telah menghadapi perang saudara dari tahun 2013 yang melibatkan dua kelompok etnis. Perang saudara ini mengakibatkan korban sebanyak 400.000 jiwa dan memaksa sepertiga dari populasi negara tersebut untuk mengungsi. Konflik ini juga mengakibatkan pendidikan di Sudan Selatan menjadi terganggu. Artikel ini bertujuan untuk menganalisis peran organisasi internasional UNICEF sebagai norm entrepreneur dalam bidang pendidikan di Sudan Selatan. Penelitian ini menggunakan metode penelitian kualititif dengan melakukan studi literatur. Hasil penelitian menemukan bahwa UNICEF dengan Back to Learning Initiative dapat mengubah pandangan masyarakat Sudan Selatan mengenai pendidikan, memberikan akses pendidikan kepada anak-anak yang putus sekolah, serta meningkatkan lingkungan pendidikan di Sudan Selatan. Kata kunci: Sudan Selatan; norm entrepreneur; pendidikan; UNICEF; Back to Learning   Abstract South Sudan has faced a civil war since 2013 involving two ethnic groups. This civil war resulted in the loss of 400,000 lives and forced a third of the country’s population to flee. The conflict has also disrupted education in South Sudan. This article aims to analyze the role of the international organization UNICEF as a norm entrepreneur in the field of education in South Sudan. This research uses a qualitative research method by conducting a literature study. The results found that UNICEF with the Back to Learning Initiative can change the views of the people of South Sudan about education, provide access to education to children who drop out of school, and improve the educational environment in South Sudan. Keywords: South Sudan; norm entrepreneur; education; UNICEF; Back to Learning